Isolates and antibiotic susceptibilities of endogenous bacterial endophthalmitis: A retrospective multicenter study in Japan. Issue 6 (June 2018) - Todokoro, Daisuke; Mochizuki, Kiyofumi; Nishida, Takashi; Eguchi, Hiroshi; Miyamoto, Tatsuro; Hattori, Takaaki; Suzuki, Takashi; Inoue, Tomoyuki; Nejima, Ryohei; Hoshi, Saichi; Akiyama, Hideo
Abstract: Endogenous bacterial endophthalmitis, also called metastatic endophthalmitis, is a rare bacterial endophthalmitis derived from distant infectious foci via the bloodstream. This infection can potentially cause not only severe visual disturbance, but also loss of the eyeball or death, as most patients are immunocompromised. This retrospective Japanese multicenter study analyzed 32 eyes in 25 definitive cases. Twelve patients (48.0%) had diabetes mellitus. Typical ocular findings were vitreous haze (87.5%), cells in the anterior chambers (62.5%) and retinal infiltrates (50.0%). Elevated body temperature (64.0%), high serum C-reactive protein (96.0%) and leukocytosis (52.0%) were also frequently observed. Culture positivity rates for intraocular fluid were higher in the vitreous (62.5%) versus aqueous humor (28.6%). High positivity rates were also observed for blood (57.1%) and central venous catheters (100%). The most common pathogen was Staphylococcus aureus (10 cases), including methicillin-resistant S. aureus (4 cases). The next most common pathogen was Klebsiella pneumoniae (7 cases), which was highly associated with liver abscess. Compared to a previous 1991 national multicenter study, there has been a fourfold increase in the ratio of S. aureus . Antibiotic susceptibility tests revealed that all Gram-positives were susceptible to vancomycin and all Gram-negatives were susceptible to third-generation cephalosporins, imipenem/cilastatin, gentamycin and levofloxacin. Prognostic factors influencing poor visual outcome included poor initial visual acuity ( p < 0.01), K. pneumoniae ( p = 0.027) and gram-negative bacteria ( p = 0.014) as the causative bacteria. Intravitreal antibiotic injection in combination with vancomycin and ceftazidime may be applicable for use as part of the standard treatment regimen for EBE.